First, multiply each term within the parenthesis by the term outside the parenthesis:
#color(red)(3sqrt(15n))(-4sqrt(10n) + 4) =>#
#(color(red)(3sqrt(15n)) * -4sqrt(10n)) + (color(red)(3sqrt(15n)) * 4) =>#
#(color(red)(3) * -4 * color(red)(sqrt(15n))sqrt(10n)) + (4 * color(red)(3sqrt(15n))) =>#
#-12sqrt(15n)sqrt(10n) + 12sqrt(15n)#
Next, we can use this rule for radicals to multiply the radicals on the left side of the expression:
#sqrt(color(red)(a)) * sqrt(color(blue)(b)) = sqrt(color(red)(a) * color(blue)(b))#
#-12sqrt(15n)sqrt(10n) + 12sqrt(15n) =>#
#-12sqrt(15n * 10n) + 12sqrt(15n) =>#
#-12sqrt(150n^2) + 12sqrt(15n)#
Then, we can rewrite the radical on the left as:
#-12sqrt(25n^2 * 6) + 12sqrt(15n)#
Now, we can use this rule of radicals (the reverse of the above rule to complete the multiplication and simplification:
#sqrt(color(red)(a) * color(blue)(b)) = sqrt(color(red)(a)) * sqrt(color(blue)(b))#
#-12sqrt(25n^2 * 6) + 12sqrt(15n) =>#
#-12sqrt(25n^2)sqrt(6) + 12sqrt(15n) =>#
#(-12 * 5nsqrt(6)) + 12sqrt(15n) =>#
#-60nsqrt(6) + 12sqrt(15n)#